2010
DOI: 10.1016/s0140-6736(10)60484-9
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies

Abstract: SummaryBackgroundUncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances.MethodsWe undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
1,530
9
31

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,062 publications
(1,605 citation statements)
references
References 27 publications
35
1,530
9
31
Order By: Relevance
“…Our findings are more consistent with prospective studies, which have tended to adjust for confounders more comprehensively. In a large, individual participant data meta‐analysis of almost 700 000 people from predominantly Western populations, diabetes (defined variably by self‐report, medication use or fasting blood glucose levels) was associated with a doubling of risk for ischaemic heart disease in a fully adjusted model 14. In the Asia Pacific Cohort Studies Collaboration individual participant data meta‐analysis involving 161 214 participants, self‐reported diabetes was associated with a 73% excess risk of ischaemic heart disease after adjustment for sex, study and age, which persisted after further adjustment for systolic blood pressure, cholesterol, obesity and smoking 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are more consistent with prospective studies, which have tended to adjust for confounders more comprehensively. In a large, individual participant data meta‐analysis of almost 700 000 people from predominantly Western populations, diabetes (defined variably by self‐report, medication use or fasting blood glucose levels) was associated with a doubling of risk for ischaemic heart disease in a fully adjusted model 14. In the Asia Pacific Cohort Studies Collaboration individual participant data meta‐analysis involving 161 214 participants, self‐reported diabetes was associated with a 73% excess risk of ischaemic heart disease after adjustment for sex, study and age, which persisted after further adjustment for systolic blood pressure, cholesterol, obesity and smoking 15.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies have found an increased risk of ischaemic heart disease only at or above glycaemic thresholds for diabetes, impaired glucose tolerance or impaired fasting glucose 14. An individual participant data meta‐analysis, including > 250 000 participants without known diabetes and ~13 000 ischaemic heart disease events, found a significantly elevated risk only at fasting blood glucose levels > 6.1 mmol/l 14. Other studies, however, have reported a significant positive association within the ‘normoglycaemic’ range 19; the Asia Pacific Cohort Studies Collaboration found a log‐linear association with ischaemic heart disease extending down to a fasting blood glucose level of 4.9 mmol/l 19.…”
Section: Discussionmentioning
confidence: 99%
“…This is a tremendous change when compared with the data from 20 years ago, when the prevalence of diabetes and impaired glucose tolerance in China were just 2.5% and 3.2%, respectively1, 3. As one of the major risk factors of disabling and life‐threatening complications from microvascular and macrovascular diseases and even cancer4, 5, 6, 7, this chronic disease is now more of a public health challenge than a health issue for individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is associated with a high prevalence of atherosclerotic cardiovascular disease (ASCVD), including coronary heart disease, ischaemic stroke and peripheral arterial disease, and ASCVD is the main cause of mortality and morbidity among those with DM 1, 2, 3. Furthermore, individuals with both DM and ASCVD represent a particularly high‐risk group, with a higher risk of further ASCVD events compared with individuals with ASCVD but without DM 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%